Allergen immunotherapy for the treatment of respiratory allergies in the elderly. Issue 4 (August 2017) - Hur, Gyu-Young; Lee, Ji-Ho; Park, Hae-Sim
Abstract : Purpose of review: Respiratory allergies, including asthma and allergic rhinitis can also occur in the elderly. Allergen immunotherapy for allergic diseases is the only disease-modifying treatment for patients with allergies available thus far. Here, we review current evidence supporting the use of allergen immunotherapy in the elderly and discuss its efficacy and utility for the treatment of respiratory allergic diseases in this setting. Recent findings: Subcutaneous and/or sublingual immunotherapy are effective therapeutic options in not only young but also older patients. Allergen immunotherapy reduces medication and symptom scores in the elderly and can thus be safely prescribed in this population. Summary: Elderly individuals with proven, clinically relevant immunoglobulin E sensitization to inhalant allergens may benefit from allergen immunotherapy for respiratory allergic diseases. Older patients without contraindications should therefore be considered for treatment, with the additional benefit of reduced medication and symptom scores.